The optimization on flow scheme of helium liquefier with genetic algorithm. (January 2017) - Wang, H.R.; Xiong, L.Y.; Peng, N.; Liu, L.Q.
Highlights: Genetic algorithm is used on the two classical schema of helium liquefier to find out the optimal parameters of the system. The given constrains are conservation law, the second law of thermodynamics. The optimal solutions are found to get the maximum liquefaction rate at the given constrains. Another new scheme is put forward to overcome the shortcomings of these two classical schemes. Genetic algorithm is also used to found the optimal solution. An total comparison of the system including efficiency, economic performance, compactness of the system and the reliability between these three schemes are conducted. The conclusions have significant meaning for the future optimal design of the large helium liquefiers, some useful rules of choosing scheme for helium liquefier are drawn in the end by comparing these three cycles. Abstract: There are several ways to organize the flow scheme of the helium liquefiers, such as arranging the expanders in parallel (reverse Brayton stage) or in series (modified Brayton stages). In this paper, the inlet mass flow and temperatures of expanders in Collins cycle are optimized using genetic algorithm (GA). Results show that maximum liquefaction rate can be obtained when the system is working at the optimal parameters. However, the reliability of the system is not well due to high wheel speed of the first turbine. Study shows that the scheme in which expanders are arranged in series with heat exchangers between them has higher operation reliability but lower plant efficiency when working at the same situation. Considering both liquefaction rate and system stability, another flow scheme is put forward hoping to solve the dilemma. The three configurations are compared from different aspects, they are respectively economic cost, heat exchanger size, system reliability and exergy efficiency. In addition, the effect of heat capacity ratio on heat transfer efficiency is discussed. A conclusion of choosing liquefier configuration is given in the end, which is meaningful for the optimal design of helium liquefier.